The dark tetrad, intimate partner violence and the mediating role of moral disengagement - Carter, L.J. (2019)
Research suggests that Intimate Partner Violence (IPV), including physical, psychological, and/or sexual abuse, is related to the dark triad (DT) traits. This study extends these findings by considering the addition of everyday sadism into the four-dimension dark tetrad (DTET) and the possibility of outside factors, such as moral disengagement (MD), which may mediate this relationship. It was also examined whether the DTET added incremental validity to more general aspects of personality (the HEXACO dimensions) in predicting IPV. Males and females (N=416) from the general population completed five questionnaires in an online survey. A factor-analysis found that sexual IPV did not load as an individual factor so was excluded from this study. Four hierarchical multiple regressions were conducted, finding that only psychopathy predicted physical IPV, however, psychopathy and Machiavellianism significantly predicted psychological IPV, with MD mediating both these relationships. Although the DTET as a whole added incremental validity over the HEXACO dimensions to predict physical IPV, this was not the case for HEXACO traits like high Emotionality, low Openness, and low Agreeableness, as Agreeableness was the best predictor of psychological IPV